Grand dishes : recipes and stories from grandmothers of the world - Miari, Anastasia; Lupton, Iska (Unbound, 2021)
There is no food quite like a grandmother<U+2019>s time-perfected dish. Inspired by their own grandmothers <U+2013> and the love they shared through the food they served <U+2013> Anastasia Miari and Iska Lupton embarked on a mission: from Corfu to Cuba, Moscow to New Orleans, and many more in between, they set out to capture cooking methods, regional recipes and timeless wisdom from grandmothers around the world.